2018
DOI: 10.1016/j.ijcha.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

VE/VCO2 slope in lean and overweight women and its relationship to lean leg mass

Abstract: Ventilation/carbon dioxide production (VE/VCO2slope) is used clinically to determine cardiorespiratory fitness and morbidity in heart failure (HF). Previously, we demonstrated that lower lean leg mass is associated with high VE/VCO2slope during exercise in HF. In healthy individuals, we evaluated 1) whether VE/VCO2slope differed between lean and overweight women and 2) the relationship between lean leg mass and VE/VCO2slope in overweight sedentary (OWS), overweight trained (OWTR) and lean, trained (LTR) women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…However, increases in the VE/VCO 2 slope values have been associated with unfavorable prognosis in patients with cardiovascular disease, particularly heart failure [53]. On the other hand, VE/VCO 2 slope was not useful to discriminate higher vs. lower values of VO 2MAX in healthy women with overweight [54]. In addition, Kemps et al [51], did not find post-intervention differences in VE/VCO 2 slope between a group of sedentary patients with stable CHF who remained sedentary and a group of individuals with similar characteristics trained with a combination of interval intensity cycling and muscle resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in the VE/VCO 2 slope values have been associated with unfavorable prognosis in patients with cardiovascular disease, particularly heart failure [53]. On the other hand, VE/VCO 2 slope was not useful to discriminate higher vs. lower values of VO 2MAX in healthy women with overweight [54]. In addition, Kemps et al [51], did not find post-intervention differences in VE/VCO 2 slope between a group of sedentary patients with stable CHF who remained sedentary and a group of individuals with similar characteristics trained with a combination of interval intensity cycling and muscle resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between minute ventilation and carbon dioxide production (VE/VCO 2 ) is a measure of cardiorespiratory efficiency and leads prognosis in cardiovascular disorders [23,[26][27][28]. VE/VCO 2 slope is independent of subject effort and BMI [29] and has been explored in different studies on lean and obese patients [15,[29][30][31][32]. Accordingly, we reported normal VE/VCO 2 slope.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, Keller-Ross et al reported that minimum VE/V CO2 and RER affected by increasing V CO2 were related to the type of bers in skeletal muscle. 20 Therefore, it was suggested that the increased RER and minimum VE/V CO2 in the not-completed group may have been caused by reduced skeletal muscle, which resulted in decreased exercise endurance time in CLET, and that the minimum VE/V CO2 was the most accurate variable to predict exercise endurance time in logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%